Prey-mimetism in cercariae of Apatemon (Digenea, Strigeidae) in freshwater in northern latitudes - Faltýnková, Anna; Kudlai, Olena; Pantoja, Camila; Jouet, Damien; Skírnisson, Karl (Parasitology research, 2023)
Cercariae, the free-living larval stages of trematodes, have adopted an amazing variety of transmission strategies. One of them is prey-mimetism, i.e. cercariae mimicking prey to attract motile hosts to be eaten. In a period between 2002 and 2019, we examined small planorbid snails, Bathyomphalus contortus, Gyraulus parvus and Planorbis planorbis from lakes in Finland and Iceland and from the Curonian Lagoon in Lithuania. Cercariae with conspicuously enlarged tails and unusual swimming behaviour, likely mimicking invertebrate prey, were detected and studied by the use of morphological and molecular (cox1, ITS1-5.8S-ITS2 and 28S rDNA) methods. Cercariae of two species belonging to the genus Apatemon (Strigeidae) were recognised. We consider Apatemon sp. 5 ex P. planorbis from the Curonian Lagoon identical to Cercaria globocaudata U. Szidat, 1940. Cercariae ex G. parvus from Iceland and ex B. contortus from Finland were conspecific, and we named them Apatemon sp. 6; these cercariae could not be associated with any known species. For the first time, we verified that cercariae of the Bulbocauda group belong to the genus Apatemon. We provide a mini-review on records of furcocercariae of the family Strigeidae with enlarged tails reported in freshwaters of the northern hemisphere and reveal that it is not only Apatemon but also Australapatemon and most likely Strigea which belong to the Bulbocauda group, rendering it a purely ecological assemblage. Understanding which invertebrate swimming behaviour these cercariae are mimicking will enhance our knowledge of the processes behind trematode transmission and will help to assess evolutionary pathways of host-finding strategies in trematodes.
Keywords: Trematoda; jezera; hlemýždi; Behaviour; Animals; Cercaria; Freshwater; Digenea; Lakes; zvířata; cerkárie; Snails; Europe; Nuclear and mitochondrial DNA